Comparison of Single-Port Versus Standard Multiport Left Lateral Liver Sectionectomy. (April 2018) - Struecker, Benjamin; Haber, Philipp; Öllinger, Robert; Bahra, Marcus; Pascher, Andreas; Pratschke, Johann; Schmelzle, Moritz
It remains unclear if single incision laparoscopic liver surgery is superior to standard multiport resections and in what regard patients might benefit from this approach. We retrospectively analyzed the course of all patients undergoing laparoscopic left lateral sectionectomy at our center between 2009 and 2017. In total, 11 single incision and 31 multiport left lateral sectionectomies were performed at our center between July 2009 and May 2017. Six patients were excluded due to multivisceral resections. Indications included adenoma (n = 7 vs n = 2), focal nodular hyperplasia (n = 4 vs n = 3), hepatocellular carcinoma (n = 4 vs n = 4), colorectal liver metastasis (n = 4 vs n = 0), noncolorectal metastasis (n = 2 vs n = 1), hemangioma (n = 3 vs n = 0), abscess (n = 1 vs n = 0), and cysts (n = 1 vs n = 0). Length of operation was significantly shorter in the single incision group (206 vs 137 minutes, P = .003). One complication was observed in the single incision group (grade IIIb, n = 1) while 3 patients in the multiport group suffered from postoperative complications (grade II, n = 1; grade IIIa, n = 2), resulting in a morbidity rate of 12.5% and 11.5%, respectively. No mortality was observed in both groups. Length of hospital stay did not significantly differ in both groups (median 7 vs 7 days, P = .513). The single incision approach is safe and has become the standard approach for the left lateral sectionectomy at our center. Shorter operation times technique might well be due to the easy retrieval of the liver specimen via the umbilical incision with no need for a Pfannenstiel incision.